Cultura Alimentaria y Turismo Gastronómico en la Ciudad de Riobamba, Provincia de Chimborazo. - López Solórzano, Andrea (2023)
The study analyzes the food culture and its relationship with gastronomic tourism in Riobamba, Chimborazo province, which has not been subject to recent research and for years has been relegated to a complementary axis in the tourist activity, the study is conducted through a documentary review and analysis of dimensions that are part of the food culture, such as representations, cultural identity and food traceability. For this purpose, the documentary and descriptive research method was used, with a quali-quantitative and correlational, non-experimental approach, in addition, field research was carried out by applying surveys to the owners of food and beverage establishments and to the inhabitants of the city, the results allowed the verification of the hypotheses. Based on the results of the application of the surveys, it was possible to conclude that the inhabitants Riobamba have a medium-low knowledge of the dimensions of the dependent variable, while the owners of the food and beverage establishments consider the application of ancestral techniques for the preparation of typical dishes and food traceability to ensure quality products to be fundamental. Finally, it is concluded as a proposal to determine strategies to safeguard the food culture of Riobamba for the benefit of gastronomic tourism.